A depressão no processo de maternidade - estudo prospectivo de mulheres da 36.ª semana de gravidez, 2.ª e 6.ª semana pós-natal - Ferreira, António Manuel dos Santos (2007)
The main purposes of this study were to study the prevalence of Postnatal Depression in a population of Portuguese mothers of the region of Porto, and to analyze its association with selected psychosocial variables. Therefore, we conducted an investigation at the prenatal consultation of Hospital S. Sebastião, in Vila da Feira, including 66 pregnant women, prospectively followed from 36th week of pregnancy until 6th week postpartum. All the participants were thoroughly informed about the purposes and the methodologies and filled a formal consent, before beginning their participation in the study. In this research, we used the following assessment instruments: the Hospital Anxiety and Depression Scale, Zigmond e Snaith, for evaluating the symptoms of anxiety and depression; the Edinburgh Postnatal Depression Scale, Cox, Holden, Sagovki, for the detection of depression; the Eysenk Personality Inventory, Eysenck e Eysenck, for the measurement of personality traits; the Social Support Network Inventory, Flaherty, Gaviria, Pathak, for the assessment of size and functioning of the social support network; the Graffar Scale and interview for the assessment of social economic strata; and, finally, we constructed a questionnaire to collect other socio-demographic and clinical data. At 36th week of pregnancy, women filled Graffar, socio-demographic questionnaire, SSNI, HADS and EPDS, and they received a set of questionnaires to be filled and returned by mail to us, at 2nd and 6th week after birth. To avoid blank questionnaires and drop-outs, we contacted every women by phone, to remember them about the moment of filling the questionnaires. Our results showed a postnatal peak on the prevalence of depression, specially at 6 weeks after birth. They emphasized also an association of postnatal depression with neurotic traits, small and malfunctioning social support network and previous eutocic delivery. Compared to their partners, women have higher prevalence of depression and seem to raise their proneness to depress whenever their husbands were depressed.